Attention Guidance through Video Script: A Case Study of Object Focusing on 360º VR Video Tours - Silva, Paulo Vitor Santana; Vitória, Arthur Ricardo Sousa; Silva, Diogo Fernandes Costa; Galvão Filho, Arlindo Rodrigues (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Within the expansive domain of virtual reality (VR), 360º VR videos immerse viewers in a spherical environment, allowing them to explore and interact with the virtual world from all angles. While this video representation offers unparalleled levels of immersion, it often lacks effective methods to guide viewers’ attention toward specific elements within the virtual environment. This paper combines the models Grounding Dino and Segment Anything (SAM) to guide attention by object focusing based on video scripts. As a case study, this work conducts the experiments on a 360º video tour on the University of Reading. The experiment results show that video scripts can improve the user experience in 360º VR Videos Tour by helping in the task of directing the user’s attention.